2021
DOI: 10.1177/0021909620983586
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Outbreak in North Africa: A Legal Analysis

Abstract: North African nations, especially Egypt, Algeria, and Morocco, have been heavily affected by COVID-19 if compared to other African countries. Governments in North Africa took proactive legal measures to manage the virus threat, safeguarding population health, but also triggering repressive and invasive mechanisms that in some cases jeopardized basic freedoms and rights. This work will analyze comparatively the anti-COVID-19 legislations, pointing out how the legislative measures mirrored the level of transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this circumstance, it is conceivable that public health measures to contain the pandemic, such as isolation and movement controls, will exacerbate already precarious social grounds. Likewise, lessons learnt from public protests during the Arab uprising in Egypt, Libya, Tunisia and the disputed Western Sahara would urge current incumbents in the region to contrive social support schemes to maintain calm and public order ( El Amine and Saghir, 2020 , Tamburini, 2021 , Trunov, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this circumstance, it is conceivable that public health measures to contain the pandemic, such as isolation and movement controls, will exacerbate already precarious social grounds. Likewise, lessons learnt from public protests during the Arab uprising in Egypt, Libya, Tunisia and the disputed Western Sahara would urge current incumbents in the region to contrive social support schemes to maintain calm and public order ( El Amine and Saghir, 2020 , Tamburini, 2021 , Trunov, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some studies (mainly from Canada and the USA) showed that suburban areas had higher rates than the major larger city [ 49 , 50 , 51 ]. In our case, the most logical explanation is non-compliance with the protective measures, especially in a political and social context historically tense in this geographical area [ 33 ]. Another expected result comes from the fact that in the Algerian regions in the northeast, where the population is concentrated, is the region with the highest rate of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (5) allows us to make inferences from the distribution of the parameter θ conditional on the observations , called the a posteriori distribution [ 33 ], and is defined by: …”
Section: Methodsmentioning
confidence: 99%
“…Egypt announced its first confirmed COVID-19 case on February 14, 2020, and has since implemented measures such as evacuating Egyptian citizens from heavily infected countries, closing schools and universities, and enforcing home-based work for civil servants ( 8 , 9 ). A confinement law banning all public meetings and gatherings was also implemented on March 24, 2020 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%